Insulation auxiliary agent for metal soft magnetic material, metal soft magnetic core and preparation method of metal soft magnetic core
The insulating additives are prepared by ball-milling composite of nano-scale gas-phase white carbon black and silicone resin, which solves the problems of complex preparation process and poor performance of metal soft magnetic materials in the prior art, and achieves more efficient insulation effect and DC bias. Performance, suitable for industrial production.
Patent Information
- Application Number
- CN202411308560.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-31
AI Technical Summary
The preparation process of existing metal soft magnetic materials is complicated, resulting in unsatisfactory hysteresis loss and DC bias performance, and is not suitable for industrial production.
Nano-level gas-phase white carbon black and silicone resin are used for ball milling to prepare an insulating additive for metal soft magnetic materials, which is used to mix with metal soft magnetic powder to form a uniform organic insulating layer to reduce the vortex between magnetic powder particles. Loss and improves DC bias performance.
The preparation process is simplified, the insulation performance and resistivity are improved, the loss of the magnetic core is significantly reduced and the DC bias performance is improved, making it suitable for industrial production.
Smart Images

Figure BDA0005049978810000141 
Figure BDA0005049978810000151 
Figure BDA0005049978810000152
Abstract
Description
Technical Field
[0001] The invention relates to the field of metal soft magnetic materials, and in particular to an insulating auxiliary agent for metal soft magnetic materials, a metal soft magnetic core and a preparation method thereof. Background Art
[0002] As the main material of key electronic components, metal soft magnetic materials are particularly important in the context of the rapid development of electronic information technology. Metal soft magnetic materials with excellent properties, such as low loss, high DC bias performance, and miniaturization, have become a research hotspot.
[0003] At present, soft magnetic metal materials usually need to be treated with insulation coating to improve their surface resistivity, thereby reducing their loss performance. The insulating coating agent is generally selected from passivation liquids such as phosphoric acid and chromic acid to react on the surface of the metal magnetic powder to form a passivation film, thereby increasing the resistivity of the magnetic powder; for example: a low-loss soft magnetic powder core and its preparation method disclosed in Chinese patent document CN 111370193 A, which uses passivation agents such as phosphoric acid, boric acid, dihydrogen phosphate and additives such as kaolin, aluminum hydroxide, and magnesium hydroxide to be dispersed in water to insulate and fill the magnetic powder, and then uses organic silica gel water as a binder, and finally obtains the soft magnetic powder core through processes such as pressing, molding, and annealing. The above method uses an inevitable acidification reaction, which will reduce the saturation flux density of the magnetic powder; moreover, the dispersion degree of kaolin in water is low, and it is difficult to mix evenly with the magnetic powder, resulting in the performance of the prepared soft magnetic metal material is not ideal; and the above process is relatively complicated and not suitable for mass production.
[0004] The prior art also discloses a method of mixing inorganic powders such as aluminum oxide and magnesium oxide with metal magnetic powders to increase the air gap and resistivity between the metal magnetic powders to reduce the core loss and improve the DC bias performance. For example, Chinese patent document CN 113724957 A discloses a soft magnetic powder core and a preparation method thereof, wherein the composite powder comprises soft magnetic powder and an insulating coating structure, wherein the insulating coating structure of the soft magnetic powder is insulated and coated with magnesium oxide and an organic binder, thereby improving the resistivity of the soft magnetic powder. However, there is a problem of uneven coating during the coating process, resulting in a high power loss.
[0005] The prior art also discloses a silicone resin made of MQ silicone resin, precipitated white carbon black, mercaptopropylmethyldimethoxysilane and HMPA through vacuum heating treatment; the silicone resin has a high decomposition temperature and strong insulation and heat resistance, so it can increase the heat treatment temperature of the metal soft magnetic powder core, while ensuring the insulation effect and further reducing the hysteresis loss of the soft magnetic material. However, its preparation process is complicated, especially the preparation process requires a vacuum environment to prepare a finished product that meets the requirements of reducing the hysteresis loss of the soft magnetic material, which is not conducive to industrial production. Summary of the invention
[0006] Therefore, the technical problem to be solved by the present invention is how to overcome the defect that the insulating additives disclosed in the prior art that can significantly reduce the hysteresis loss and DC bias performance of soft magnetic materials have complex production and are not conducive to industrial production, thereby providing an insulating additive for metal soft magnetic materials, a metal soft magnetic core and a preparation method thereof to solve the above problems.
[0007] The invention discloses a method for preparing an insulating auxiliary agent for metal soft magnetic materials, which is prepared by ball-milling and compounding nano-grade fumed silica and organic silicon resin.
[0008] The amount of the nano-scale fumed silica used is more than 0.05wt.% of the silicone resin, preferably 0.1wt.% to 2wt.%, more preferably 0.2wt.% to 1wt.%; for example: the amount of the nano-scale fumed silica used is 0.1wt.%, 0.3wt.%, 0.5wt.%, 0.7wt.%, 0.9wt.%, 1.0wt.%, 1.5wt.%, 2.0wt.%, etc. of the silicone resin.
[0009] And / or, the silicone resin is at least one of a polyalkyl silicone resin, a polyaryl silicone resin, and a polyalkylaryl silicone resin.
[0010] The method for preparing the insulating auxiliary agent for metallic soft magnetic materials of the present invention comprises:
[0011] Dispersing nano-sized fumed silica in a solvent to form a slurry;
[0012] The slurry is mixed with the silicone resin and ball-milled to obtain an insulating additive;
[0013] The nano-scale fumed silica is dispersed in the solvent by ball milling, and / or the slurry and the silicone resin are mixed by ball milling.
[0014] The ball milling time of the nano-scale fumed silica and the solvent is 2 to 6 hours; for example, the ball milling time is 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, etc.
[0015] And / or, the solvent includes one or more of ethanol, propanol, and acetone;
[0016] And / or, the ball milling time of the slurry and the silicone resin is 5 to 10 hours; for example, the ball milling time is 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, etc.
[0017] The nano-scale fumed silica is 1wt.% to 10wt.% of the weight of the solvent; for example, the nano-scale fumed silica is 1wt.%, 2wt.%, 3wt.%, 4wt.%, 5wt.%, 6wt.%, 7wt.%, 8wt.%, 9wt.%, 10wt.%, etc., of the weight of the solvent.
[0018] And / or, the solid content of the silicone resin is 50% to 60%; for example: the solid content is 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, etc.
[0019] The rotation speed of the ball mill is 1500-2500 rpm; for example, the rotation speed is 1500 rpm, 1600 rpm, 1700 rpm, 1800 rpm, 1900 rpm, 2000 rpm, 2100 rpm, 2200 rpm, 2300 rpm, 2400 rpm, 2500 rpm, etc.
[0020] An insulating auxiliary agent for metallic soft magnetic materials is prepared by adopting the above-mentioned preparation method.
[0021] A metal soft magnetic composite material comprises metal soft magnetic powder and the above-mentioned insulating auxiliary agent.
[0022] The added amount of the insulating auxiliary agent is more than 0.5% of the weight of the metal soft magnetic powder, preferably 0.5% to 4%, and more preferably 0.7% to 2.5%; for example: the added amount is 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, etc.
[0023] A metal soft magnetic core is prepared by using the metal soft magnetic composite material.
[0024] The technical solution of the present invention has the following advantages:
[0025] 1. The present invention provides a method for preparing an insulating auxiliary agent for a metal soft magnetic material, which can be directly compounded by dispersing ultrafine nano-scale fumed silica in an organic silicone resin through ball milling. The insulating auxiliary agent obtained after compounding not only improves the insulating properties of the organic silicone resin, but also has good dispersibility and uniformity, as well as high resistivity; applying it to the metal soft magnetic material can obtain a better coating effect, and while achieving the insulation effect itself, it can also effectively and significantly reduce the eddy current loss between magnetic powder particles and improve its DC bias performance; and the preparation method of the present invention is simpler, and only ball milling is required, without the need for vacuum, heat treatment and other conditions, and is very suitable for industrial mass production.
[0026] 2. The present invention provides a metal soft magnetic composite material. Since the insulating additive for metal soft magnetic material in the present invention is used, based on the fact that the insulating additive for metal soft magnetic material has both insulating effect and bonding effect, the insulating additive can be directly mixed with metal soft magnetic powder without adding other additives or performing material addition processing in several steps. This greatly simplifies the preparation process of metal soft magnetic materials and improves production efficiency. DETAILED DESCRIPTION
[0027] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0028] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0029] Example 1
[0030] A metal soft magnetic core, the preparation method of which is as follows:
[0031] (1) Weighing and mixing nano-sized fumed silica and anhydrous ethanol, wherein the mass of the fumed silica is 8 wt.% of the anhydrous ethanol; and milling the mixture in a planetary ball mill at a rotation speed of 1500 rpm for 3 h to obtain an anhydrous ethanol slurry of the fumed silica.
[0032] (2) The obtained anhydrous ethanol slurry of white carbon black and polyalkyl silicone resin are ball-milled in a planetary ball mill at a ball-milling speed of 1500 rpm for 5 h, and the mass of the anhydrous ethanol slurry of white carbon black is 10 wt.% of the polymethyl silicone resin. The polyalkyl silicone resin in this embodiment is a polymethyl silicone resin with a solid content of 60% produced by Hubei Longsheng Sihai New Materials Co., Ltd.
[0033] (3) dispersing the prepared insulating agent in acetone, adding sendustine soft magnetic powder, stirring and ultrasonic treatment for 10 minutes, so that the metal soft magnetic powder and the solution are evenly and fully mixed, and an organic insulating layer is formed on the surface of the metal soft magnetic powder; wherein the mass ratio of the insulating agent to acetone is 1:3, and the mass of the insulating agent is 1% of the mass of the sendustine soft magnetic powder.
[0034] (4) sieving the prepared metal soft magnetic composite material through a 60-mesh sieve to form particles and drying them in a 60° C. air drying oven;
[0035] (5) 0.5% zinc stearate demolding powder was added and pressed under a pressure of 1500 MPa to form a magnetic powder core with OD = 12.75 mm, ID = 7.60 mm, and Ht = 3.60 mm. The pressed magnetic powder core was placed in a nitrogen atmosphere at 720°C for heat treatment for 60 min, and then the soft magnetic properties were tested.
[0036] Example 2
[0037] A metal soft magnetic core, the preparation method of which is as follows:
[0038] (1) Weighing and mixing nano-sized fumed silica and anhydrous ethanol, wherein the mass of the fumed silica is 6 wt.% of the anhydrous ethanol; and milling the mixture in a planetary ball mill at a rotation speed of 1500 rpm for 3 h to obtain an anhydrous ethanol slurry of the fumed silica.
[0039] (2) The obtained anhydrous ethanol slurry of white carbon black and polyalkyl silicone resin are ball-milled in a planetary ball mill at a ball-milling speed of 1500 rpm for 5 h, and the mass of the anhydrous ethanol slurry of white carbon black is 10 wt.% of the polymethyl silicone resin. The polyalkyl silicone resin in this embodiment is a polymethyl silicone resin with a solid content of 60% produced by Hubei Longsheng Sihai New Materials Co., Ltd.
[0040] (3) dispersing the prepared insulating agent in acetone, adding sendustine soft magnetic powder, stirring and ultrasonic treatment for 10 minutes, so that the metal soft magnetic powder and the solution are evenly and fully mixed, and an organic insulating layer is formed on the surface of the metal soft magnetic powder; wherein the mass ratio of the insulating agent to acetone is 1:3, and the mass of the insulating agent is 1% of the mass of the sendustine soft magnetic powder.
[0041] (4) sieving the prepared metal soft magnetic composite material through a 60-mesh sieve to form particles and drying them in a 60° C. air drying oven;
[0042] (5) 0.5% zinc stearate demolding powder was added and pressed under a pressure of 1500 MPa to form a magnetic powder core with OD = 12.75 mm, ID = 7.60 mm, and Ht = 3.60 mm. The pressed magnetic powder core was placed in a nitrogen atmosphere at 720°C for heat treatment for 60 min, and then the soft magnetic properties were tested.
[0043] Example 3
[0044] A metal soft magnetic core, the preparation method of which is as follows:
[0045] (1) Weighing and mixing nano-sized fumed silica and anhydrous ethanol, wherein the mass of the fumed silica is 5 wt.% of the anhydrous ethanol; and milling the mixture in a planetary ball mill at a rotation speed of 1500 rpm for 3 h to obtain an anhydrous ethanol slurry of the fumed silica.
[0046] (2) The obtained anhydrous ethanol slurry of white carbon black and the polyalkyl silicone resin are ball-milled in a planetary ball mill at a ball-milling speed of 1500 rpm for 5 h. The mass of the anhydrous ethanol slurry of white carbon black is 10 wt.% of the polymethyl silicone resin. The polyalkyl silicone resin in this embodiment is a polymethyl silicone resin polyalkyl silicone resin with a solid content of 60% produced by Hubei Longsheng Sihai New Materials Co., Ltd.
[0047] (3) dispersing the prepared insulating agent in acetone, adding sendustine soft magnetic powder, stirring and ultrasonic treatment for 10 minutes, so that the metal soft magnetic powder and the solution are evenly and fully mixed, and an organic insulating layer is formed on the surface of the metal soft magnetic powder; wherein the mass ratio of the insulating agent to acetone is 1:3, and the mass of the insulating agent is 1% of the mass of the sendustine soft magnetic powder.
[0048] (4) sieving the prepared metal soft magnetic composite material through a 60-mesh sieve to form particles and drying them in a 60° C. air drying oven;
[0049] (5) 0.5% zinc stearate demolding powder was added and pressed under a pressure of 1500 MPa to form a magnetic powder core with OD = 12.75 mm, ID = 7.60 mm, and Ht = 3.60 mm. The pressed magnetic powder core was placed in a nitrogen atmosphere at 720°C for heat treatment for 60 min, and then the soft magnetic properties were tested.
[0050] Example 4
[0051] A metal soft magnetic core, the preparation method of which is as follows:
[0052] (1) Weighing and mixing nano-sized fumed silica and anhydrous ethanol, wherein the mass of the fumed silica is 4 wt.% of the anhydrous ethanol; and milling the mixture in a planetary ball mill at a rotation speed of 1500 rpm for 3 h to obtain an anhydrous ethanol slurry of the fumed silica.
[0053] (2) The obtained anhydrous ethanol slurry of white carbon black and polyalkyl silicone resin are ball-milled in a planetary ball mill at a ball-milling speed of 1500 rpm for 5 h, and the mass of the anhydrous ethanol slurry of white carbon black is 10 wt.% of the polymethyl silicone resin. The polyalkyl silicone resin in this embodiment is a polymethyl silicone resin with a solid content of 60% produced by Hubei Longsheng Sihai New Materials Co., Ltd.
[0054] (3) dispersing the prepared insulating agent in acetone, adding sendustine soft magnetic powder, stirring and ultrasonic treatment for 10 minutes, so that the metal soft magnetic powder and the solution are evenly and fully mixed, and an organic insulating layer is formed on the surface of the metal soft magnetic powder; wherein the mass ratio of the insulating agent to acetone is 1:3, and the mass of the insulating agent is 1% of the mass of the sendustine soft magnetic powder.
[0055] (4) sieving the prepared metal soft magnetic composite material through a 60-mesh sieve to form particles and drying them in a 60° C. air drying oven;
[0056] (5) 0.5% zinc stearate demolding powder was added and pressed under a pressure of 1500 MPa to form a magnetic powder core with OD = 12.75 mm, ID = 7.60 mm, and Ht = 3.60 mm. The pressed magnetic powder core was placed in a nitrogen atmosphere at 720°C for heat treatment for 60 min, and then the soft magnetic properties were tested.
[0057] Example 5
[0058] A metal soft magnetic core, the preparation method of which is as follows:
[0059] (1) Weighing and mixing nano-sized fumed silica and anhydrous ethanol, wherein the mass of the fumed silica is 10 wt.% of the anhydrous ethanol; and milling the mixture in a planetary ball mill at a rotation speed of 1500 rpm for 3 h to obtain an anhydrous ethanol slurry of the fumed silica.
[0060] (2) The obtained anhydrous ethanol slurry of white carbon black and polyalkyl silicone resin are ball-milled in a planetary ball mill at a ball-milling speed of 1500 rpm for 5 h, and the mass of the anhydrous ethanol slurry of white carbon black is 10 wt.% of the polymethyl silicone resin. The polyalkyl silicone resin in this embodiment is a polymethyl silicone resin with a solid content of 60% produced by Hubei Longsheng Sihai New Materials Co., Ltd.
[0061] (3) dispersing the prepared insulating agent in acetone, adding sendustine soft magnetic powder, stirring and ultrasonic treatment for 10 minutes, so that the metal soft magnetic powder and the solution are evenly and fully mixed, and an organic insulating layer is formed on the surface of the metal soft magnetic powder; wherein the mass ratio of the insulating agent to acetone is 1:3, and the mass of the insulating agent is 1% of the mass of the sendustine soft magnetic powder.
[0062] (4) sieving the prepared metal soft magnetic composite material through a 60-mesh sieve to form particles and drying them in a 60° C. air drying oven;
[0063] (5) 0.5% zinc stearate demolding powder was added and pressed under a pressure of 1500 MPa to form a magnetic powder core with OD = 12.75 mm, ID = 7.60 mm, and Ht = 3.60 mm. The pressed magnetic powder core was placed in a nitrogen atmosphere at 720°C for heat treatment for 60 min, and then the soft magnetic properties were tested.
[0064] Example 6
[0065] A metal soft magnetic core, the preparation method of which is as follows:
[0066] (1) Weighing and mixing nano-sized fumed silica and anhydrous ethanol, wherein the mass of the fumed silica is 1 wt.% of the anhydrous ethanol; and milling the mixture in a planetary ball mill at a rotation speed of 1500 rpm for 3 h to obtain an anhydrous ethanol slurry of the fumed silica.
[0067] (2) The obtained anhydrous ethanol slurry of white carbon black and polyalkyl silicone resin are ball-milled in a planetary ball mill at a ball-milling speed of 1500 rpm for 5 h, and the mass of the anhydrous ethanol slurry of white carbon black is 10 wt.% of the polymethyl silicone resin. The polyalkyl silicone resin in this embodiment is a polymethyl silicone resin with a solid content of 60% produced by Hubei Longsheng Sihai New Materials Co., Ltd.
[0068] (3) dispersing the prepared insulating agent in acetone, adding sendustine soft magnetic powder, stirring and ultrasonic treatment for 10 minutes, so that the metal soft magnetic powder and the solution are evenly and fully mixed, and an organic insulating layer is formed on the surface of the metal soft magnetic powder; wherein the mass ratio of the insulating agent to acetone is 1:3, and the mass of the insulating agent is 1% of the mass of the sendustine soft magnetic powder.
[0069] (4) sieving the prepared metal soft magnetic composite material through a 60-mesh sieve to form particles and drying them in a 60° C. air drying oven;
[0070] (5) 0.5% zinc stearate demolding powder was added and pressed under a pressure of 1500 MPa to form a magnetic powder core with OD = 12.75 mm, ID = 7.60 mm, and Ht = 3.60 mm. The pressed magnetic powder core was placed in a nitrogen atmosphere at 720°C for heat treatment for 60 min, and then the soft magnetic properties were tested.
[0071] Example 7
[0072] A metal soft magnetic core, the preparation method of which is as follows:
[0073] (1) Weighing and mixing nano-sized fumed silica and anhydrous ethanol, wherein the mass of the fumed silica is 8 wt.% of the anhydrous ethanol; and milling the mixture in a planetary ball mill at a rotation speed of 1500 rpm for 3 h to obtain an anhydrous ethanol slurry of the fumed silica.
[0074] (2) The obtained anhydrous ethanol slurry of white carbon black and polyalkyl silicone resin were ball-milled in a planetary ball mill at a ball-milling speed of 1500 rpm for 5 h, and the mass of the anhydrous ethanol slurry of white carbon black was 25 wt.% of the polymethyl silicone resin. The polyalkyl silicone resin in this embodiment was a polymethyl silicone resin with a solid content of 60% produced by Hubei Longsheng Sihai New Materials Co., Ltd.
[0075] (3) dispersing the prepared insulating agent in acetone, adding sendustine soft magnetic powder, stirring and ultrasonic treatment for 10 minutes, so that the metal soft magnetic powder and the solution are evenly and fully mixed, and an organic insulating layer is formed on the surface of the metal soft magnetic powder; wherein the mass ratio of the insulating agent to acetone is 1:3, and the mass of the insulating agent is 1% of the mass of the sendustine soft magnetic powder.
[0076] (4) sieving the prepared metal soft magnetic composite material through a 60-mesh sieve to form particles and drying them in a 60° C. air drying oven;
[0077] (5) 0.5% zinc stearate demolding powder was added and pressed under a pressure of 1500 MPa to form a magnetic powder core with OD = 12.75 mm, ID = 7.60 mm, and Ht = 3.60 mm. The pressed magnetic powder core was placed in a nitrogen atmosphere at 720°C for heat treatment for 60 min, and then the soft magnetic properties were tested.
[0078] Example 8
[0079] A metal soft magnetic core, the preparation method of which is as follows:
[0080] (1) Weighing and mixing nano-sized fumed silica and anhydrous ethanol, wherein the mass of the fumed silica is 8 wt.% of the anhydrous ethanol; and milling the mixture in a planetary ball mill at a rotation speed of 1500 rpm for 3 h to obtain an anhydrous ethanol slurry of the fumed silica.
[0081] (2) The obtained anhydrous ethanol slurry of white carbon black and polyalkyl silicone resin are ball-milled in a planetary ball mill at a ball-milling speed of 1500 rpm for 5 h, and the mass of the anhydrous ethanol slurry of white carbon black is 50 wt.% of the polymethyl silicone resin. The polyalkyl silicone resin in this embodiment is a polymethyl silicone resin with a solid content of 60% produced by Hubei Longsheng Sihai New Materials Co., Ltd.
[0082] (3) dispersing the prepared insulating agent in acetone, adding sendustine soft magnetic powder, stirring and ultrasonic treatment for 10 minutes, so that the metal soft magnetic powder and the solution are evenly and fully mixed, and an organic insulating layer is formed on the surface of the metal soft magnetic powder; wherein the mass ratio of the insulating agent to acetone is 1:3, and the mass of the insulating agent is 1% of the mass of the sendustine soft magnetic powder.
[0083] (4) sieving the prepared metal soft magnetic composite material through a 60-mesh sieve to form particles and drying them in a 60° C. air drying oven;
[0084] (5) 0.5% zinc stearate demolding powder was added and pressed under a pressure of 1500 MPa to form a magnetic powder core with OD = 12.75 mm, ID = 7.60 mm, and Ht = 3.60 mm. The pressed magnetic powder core was placed in a nitrogen atmosphere at 720°C for heat treatment for 60 min, and then the soft magnetic properties were tested.
[0085] Example 9
[0086] A metal soft magnetic core, the preparation method of which is as follows:
[0087] (1) Weighing and mixing nano-sized fumed silica and anhydrous ethanol, wherein the mass of the fumed silica is 8 wt.% of the anhydrous ethanol; and milling the mixture in a planetary ball mill at a rotation speed of 1500 rpm for 3 h to obtain an anhydrous ethanol slurry of the fumed silica.
[0088] (2) The obtained anhydrous ethanol slurry of white carbon black and polyaryl silicone resin were ball-milled in a planetary ball mill at a ball milling speed of 1500 rpm for 5 h, and the mass of the anhydrous ethanol slurry of white carbon black was 10 wt.% of the polymethyl silicone resin. The polyaryl silicone resin in this embodiment was a polyaryl silicone resin with a solid content of 60% produced by Hubei Longsheng Sihai New Materials Co., Ltd.
[0089] (3) dispersing the prepared insulating agent in acetone, adding sendustine soft magnetic powder, stirring and ultrasonic treatment for 10 minutes, so that the metal soft magnetic powder and the solution are evenly and fully mixed, and an organic insulating layer is formed on the surface of the metal soft magnetic powder; wherein the mass ratio of the insulating agent to acetone is 1:3, and the mass of the insulating agent is 1% of the mass of the sendustine soft magnetic powder.
[0090] (4) sieving the prepared metal soft magnetic composite material through a 60-mesh sieve to form particles and drying them in a 60° C. air drying oven;
[0091] (5) 0.5% zinc stearate demolding powder was added and pressed under a pressure of 1500 MPa to form a magnetic powder core with OD = 12.75 mm, ID = 7.60 mm, and Ht = 3.60 mm. The pressed magnetic powder core was placed in a nitrogen atmosphere at 720°C for heat treatment for 60 min, and then the soft magnetic properties were tested.
[0092] Example 10
[0093] A metal soft magnetic core, the preparation method of which is as follows:
[0094] (1) Weighing and mixing nano-sized fumed silica and anhydrous ethanol, wherein the mass of the fumed silica is 8 wt.% of the anhydrous ethanol; and milling the mixture in a planetary ball mill at a rotation speed of 1500 rpm for 3 h to obtain an anhydrous ethanol slurry of the fumed silica.
[0095] (2) The obtained anhydrous ethanol slurry of white carbon black and the polyalkyl aryl silicone resin are ball-milled in a planetary ball mill at a ball-milling speed of 1500 rpm for 5 h, and the mass of the anhydrous ethanol slurry of white carbon black is 10 wt.% of the polymethyl silicone resin. The polyalkyl aryl silicone resin in this embodiment is a polyalkyl aryl silicone resin with a solid content of 60% produced by Hubei Longsheng Sihai New Materials Co., Ltd.
[0096] (3) dispersing the prepared insulating agent in acetone, adding sendustine soft magnetic powder, stirring and ultrasonic treatment for 10 minutes, so that the metal soft magnetic powder and the solution are evenly and fully mixed, and an organic insulating layer is formed on the surface of the metal soft magnetic powder; wherein the mass ratio of the insulating agent to acetone is 1:3, and the mass of the insulating agent is 1% of the mass of the sendustine soft magnetic powder.
[0097] (4) sieving the prepared metal soft magnetic composite material through a 60-mesh sieve to form particles and drying them in a 60° C. air drying oven;
[0098] (5) 0.5% zinc stearate demolding powder was added and pressed under a pressure of 1500 MPa to form a magnetic powder core with OD = 12.75 mm, ID = 7.60 mm, and Ht = 3.60 mm. The pressed magnetic powder core was placed in a nitrogen atmosphere at 720°C for heat treatment for 60 min, and then the soft magnetic properties were tested.
[0099] Embodiment 11
[0100] A metal soft magnetic core, the preparation method of which is as follows:
[0101] (1) Weighing and mixing nano-sized fumed silica and anhydrous ethanol, wherein the mass of the fumed silica is 8 wt.% of the anhydrous ethanol; and milling the mixture in a planetary ball mill at a rotation speed of 2500 rpm for 2 h to obtain an anhydrous ethanol slurry of the fumed silica.
[0102] (2) The obtained anhydrous ethanol slurry of white carbon black and polymethyl silicone resin were ball-milled in a planetary ball mill at a rotation speed of 1500 rpm for 10 hours to obtain an insulating additive; the mass of the anhydrous ethanol slurry of white carbon black was 10wt.% of the polymethyl silicone resin. The polyalkyl silicone resin in this embodiment was a polymethyl silicone resin with a solid content of 60% produced by Hubei Longsheng Sihai New Materials Co., Ltd.
[0103] (3) dispersing the prepared insulating agent in acetone, adding sendustine soft magnetic powder, stirring and ultrasonic treatment for 10 minutes, so that the metal soft magnetic powder and the solution are evenly and fully mixed, and an organic insulating layer is formed on the surface of the metal soft magnetic powder; wherein the mass ratio of the insulating agent to acetone is 1:3, and the mass of the insulating agent is 1% of the mass of the sendustine soft magnetic powder.
[0104] (4) sieving the prepared metal soft magnetic composite material through a 60-mesh sieve to form particles and drying them in a 60° C. air drying oven;
[0105] (5) 0.5% zinc stearate demolding powder was added and pressed under a pressure of 1500 MPa to form a magnetic powder core with OD = 12.75 mm, ID = 7.60 mm, and Ht = 3.60 mm. The pressed magnetic powder core was placed in a nitrogen atmosphere at 720°C for heat treatment for 60 min, and then the soft magnetic properties were tested.
[0106] Example 12
[0107] A metal soft magnetic core, the preparation method of which is as follows:
[0108] (1) Weighing and mixing nano-sized fumed silica and anhydrous ethanol, wherein the mass of the fumed silica is 8 wt.% of the anhydrous ethanol; and milling the mixture in a planetary ball mill at a rotation speed of 1500 rpm for 6 h to obtain an anhydrous ethanol slurry of the fumed silica.
[0109] (2) The obtained anhydrous ethanol slurry of white carbon black and polymethyl silicone resin were ball-milled in a planetary ball mill at a rotation speed of 2500 rpm for 5 hours to obtain an insulating additive; the mass of the anhydrous ethanol slurry of white carbon black was 10wt.% of the polymethyl silicone resin. The polyalkyl silicone resin in this embodiment was a polymethyl silicone resin with a solid content of 60% produced by Hubei Longsheng Sihai New Materials Co., Ltd.
[0110] (3) dispersing the prepared insulating agent in acetone, adding sendustine soft magnetic powder, stirring and ultrasonic treatment for 10 minutes, so that the metal soft magnetic powder and the solution are evenly and fully mixed, and an organic insulating layer is formed on the surface of the metal soft magnetic powder; wherein the mass ratio of the insulating agent to acetone is 1:3, and the mass of the insulating agent is 1% of the mass of the sendustine soft magnetic powder.
[0111] (4) sieving the prepared metal soft magnetic composite material through a 60-mesh sieve to form particles and drying them in a 60° C. air drying oven;
[0112] (5) 0.5% zinc stearate demolding powder was added and pressed under a pressure of 1500 MPa to form a magnetic powder core with OD = 12.75 mm, ID = 7.60 mm, and Ht = 3.60 mm. The pressed magnetic powder core was placed in a nitrogen atmosphere at 720°C for heat treatment for 60 min, and then the soft magnetic properties were tested.
[0113] Embodiment 13
[0114] A metal soft magnetic core, the preparation method of which is as follows:
[0115] (1) Weighing and mixing nano-sized fumed silica and anhydrous ethanol, wherein the mass of the fumed silica is 8 wt.% of the anhydrous ethanol; and milling the mixture in a planetary ball mill at a rotation speed of 2000 rpm for 4 h to obtain an anhydrous ethanol slurry of the fumed silica.
[0116] (2) The obtained anhydrous ethanol slurry of white carbon black and polymethyl silicone resin were ball-milled in a planetary ball mill at a rotation speed of 2000 rpm for 8 hours to obtain an insulating additive; the mass of the anhydrous ethanol slurry of white carbon black was 10wt.% of the polymethyl silicone resin. The polyalkyl silicone resin in this embodiment was a polymethyl silicone resin with a solid content of 60% produced by Hubei Longsheng Sihai New Materials Co., Ltd.
[0117] (3) dispersing the prepared insulating agent in acetone, adding sendustine soft magnetic powder, stirring and ultrasonic treatment for 10 minutes, so that the metal soft magnetic powder and the solution are evenly and fully mixed, and an organic insulating layer is formed on the surface of the metal soft magnetic powder; wherein the mass ratio of the insulating agent to acetone is 1:3, and the mass of the insulating agent is 1% of the mass of the sendustine soft magnetic powder.
[0118] (4) sieving the prepared metal soft magnetic composite material through a 60-mesh sieve to form particles and drying them in a 60° C. air drying oven;
[0119] (5) 0.5% zinc stearate demolding powder was added and pressed under a pressure of 1500 MPa to form a magnetic powder core with OD = 12.75 mm, ID = 7.60 mm, and Ht = 3.60 mm. The pressed magnetic powder core was placed in a nitrogen atmosphere at 720°C for heat treatment for 60 min, and then the soft magnetic properties were tested.
[0120] Embodiment 14
[0121] A metal soft magnetic core, the preparation method of which is basically the same as that of Example 1, except that the mass of the insulating auxiliary agent is 0.5% of the mass of the sendust metal soft magnetic powder.
[0122] Embodiment 15
[0123] A metal soft magnetic core, the preparation method of which is basically the same as that of Example 1, except that the mass of the insulating auxiliary agent is 2% of the mass of the sendust metal soft magnetic powder.
[0124] Example 16
[0125] A metal soft magnetic core, the preparation method of which is basically the same as that of Example 1, except that the mass of the insulating auxiliary agent is 3% of the mass of the sendust metal soft magnetic powder.
[0126] Embodiment 17
[0127] A metal soft magnetic core, the preparation method of which is basically the same as that of Example 1, except that the mass of the insulating auxiliary agent is 4% of the mass of the sendust metal soft magnetic powder.
[0128] Comparative Example 1
[0129] A metal soft magnetic core, the preparation method of which is as follows:
[0130] (1) Weigh nano-scale fumed silica and polymethyl silicone resin, grind and mix them mechanically to obtain an insulating additive, wherein the mass of the silica is 0.4wt.% of the polymethyl silicone resin. The polymethyl silicone resin in this embodiment is a polymethyl silicone resin with a solid content of 60% produced by Hubei Longsheng Sihai New Materials Co., Ltd.
[0131] (2) dispersing the insulating agent prepared above in acetone, adding sendustine soft magnetic powder, stirring and ultrasonic treatment for 10 minutes, so that the metal soft magnetic powder and the solution are evenly and fully mixed, and an organic insulating layer is formed on the surface of the metal soft magnetic powder; wherein the mass ratio of the insulating agent to acetone is 1:3, and the mass of the insulating agent is 1% of the mass of the sendustine soft magnetic powder.
[0132] (3) sieving the prepared metal soft magnetic composite material through a 60-mesh sieve to form particles and drying them in a 60° C. forced air drying oven;
[0133] (4) 0.5% zinc stearate demolding powder was added and pressed under a pressure of 1500 MPa to form a magnetic powder core with OD = 12.75 mm, ID = 7.60 mm, and Ht = 3.60 mm. The pressed magnetic powder core was placed in a nitrogen atmosphere at 720°C for heat treatment for 60 min, and then the soft magnetic properties were tested.
[0134] Comparative Example 2
[0135] A metal soft magnetic core, the preparation method of which is as follows:
[0136] (1) Weighing and mixing precipitated silica and anhydrous ethanol, wherein the mass of the precipitated silica is 8 wt.% of the anhydrous ethanol; and milling the mixture in a planetary ball mill at a rotation speed of 1500 rpm for 3 h to obtain an anhydrous ethanol slurry of silica.
[0137] (2) The obtained anhydrous ethanol slurry of white carbon black and polymethyl silicone resin were ball-milled in a planetary ball mill at a ball-milling speed of 1500 rpm for 5 h. The mass of the anhydrous ethanol slurry of white carbon black was 10 wt.% of the polymethyl silicone resin. The polymethyl silicone resin in this embodiment was a polymethyl silicone resin with a solid content of 60% produced by Hubei Longsheng Sihai New Materials Co., Ltd.
[0138] (3) dispersing the prepared insulating agent in acetone, adding sendustine soft magnetic powder, stirring and ultrasonic treatment for 10 minutes, so that the metal soft magnetic powder and the solution are evenly and fully mixed, and an organic insulating layer is formed on the surface of the metal soft magnetic powder; wherein the mass ratio of the insulating agent to acetone is 1:3, and the mass of the insulating agent is 1% of the mass of the sendustine soft magnetic powder.
[0139] (4) sieving the prepared metal soft magnetic composite material through a 60-mesh sieve to form particles and drying them in a 60° C. air drying oven;
[0140] (5) 0.5% zinc stearate demolding powder was added and pressed under a pressure of 1500 MPa to form a magnetic powder core with OD = 12.75 mm, ID = 7.60 mm, and Ht = 3.60 mm. The pressed magnetic powder core was placed in a nitrogen atmosphere at 720°C for heat treatment for 60 min, and then the soft magnetic properties were tested.
[0141] Comparative Example 3
[0142] A metal soft magnetic core, the preparation method of which is as follows:
[0143] (1) Weigh 500-mesh kaolin powder and anhydrous ethanol and mix them, wherein the mass of the kaolin powder is 8 wt.% of the anhydrous ethanol; and grind them in a planetary ball mill at a rotation speed of 1500 rpm for 3 hours to obtain an anhydrous ethanol slurry of kaolin.
[0144] (2) The prepared kaolin anhydrous ethanol slurry and polymethyl silicone resin were ball-milled in a planetary ball mill at a ball milling speed of 1500 rpm for 5 h. The mass of the kaolin anhydrous ethanol slurry was 10 wt.% of the polymethyl silicone resin. The polymethyl silicone resin in this embodiment was a polymethyl silicone resin with a solid content of 60% produced by Hubei Longsheng Sihai New Materials Co., Ltd.
[0145] (3) dispersing the prepared insulating agent in acetone, adding sendustine soft magnetic powder, stirring and ultrasonic treatment for 10 minutes, so that the metal soft magnetic powder and the solution are evenly and fully mixed, and an organic insulating layer is formed on the surface of the metal soft magnetic powder; wherein the mass ratio of the insulating agent to acetone is 1:3, and the mass of the insulating agent is 1% of the mass of the sendustine soft magnetic powder.
[0146] (4) sieving the prepared metal soft magnetic composite material through a 60-mesh sieve to form particles and drying them in a 60° C. air drying oven;
[0147] (5) 0.5% zinc stearate demolding powder was added and pressed under a pressure of 1500 MPa to form a magnetic powder core with OD = 12.75 mm, ID = 7.60 mm, and Ht = 3.60 mm. The pressed magnetic powder core was placed in a nitrogen atmosphere at 720°C for heat treatment for 60 min, and then the soft magnetic properties were tested.
[0148] The magnetic powder cores of the above embodiments and comparative examples were tested for soft magnetic properties under the test conditions of 500kHz, 50mT and 25°C. The test results are shown in Tables 1 to 4 below.
[0149] Table 1
[0150]
[0151] From the comparison between Example 1 and Comparative Example 1, it can be seen that the metal soft magnetic material prepared by simply mechanically mixing fumed silica with metal powder and then bonding with silicone resin has high loss and low DC bias performance. This shows that mechanical mixing between powders cannot achieve a uniform coating effect.
[0152] From the comparison between Example 1 and Comparative Examples 2 and 3, it can be seen that the insulating agent prepared by precipitated silica or kaolin powder is not as effective as the insulating agent prepared by fumed silica on the treatment of metal soft magnetic powder. This is mainly because the particle size of commonly used inorganic coating agents such as precipitated silica and magnesium oxide is similar to the particle size of soft magnetic metal particles. Due to the steric hindrance effect, nano-scale fumed silica is more likely to form a coating film on the surface of micron-scale magnetic powder particles, thereby reducing the core loss.
[0153] It can be seen from the above-mentioned Example 1 and Examples 11-13 that the insulating additive prepared by mixing fumed silica and silicone resin under the ball milling process of the present invention has similar core loss and DC bias performance, and is superior to the core loss and DC bias performance data of Comparative Examples 1-3.
[0154] Therefore, by comparing the above-mentioned Example 1, Examples 11-13 with Comparative Examples 1-3, it can be seen that under the same raw material ratio, as long as the preparation process of gas-phase silica and silicone resin combined with ball milling is adopted, the insulating additive prepared can significantly reduce the core loss and improve the DC bias performance.
[0155] Table 2
[0156]
[0157] From the data of Examples 1 to 8, it can be seen that in the insulating additive, when only the amount of nano-scale fumed silica is changed and other conditions are the same, the increase in the amount of fumed silica can reduce the effective magnetic permeability of the metal soft magnetic material and improve its DC bias performance; but the study found that the loss of the metal soft magnetic material first decreases and then increases with the increase in the amount of fumed silica, that is, the excessive amount of fumed silica will increase the loss of the metal soft magnetic material. The reason for this result may be that the insulating additive prepared by too little silica is difficult to form an insulating layer with a high resistivity, thereby failing to reduce its eddy current loss; and the excessive amount of silica will increase the viscosity of the additive and cannot be evenly dispersed in the silicone resin, making it difficult to achieve a stable and uniform coating effect. Therefore, in order to obtain relatively high DC bias performance and lower loss; the amount of the nano-scale fumed silica in the insulating additive of the present invention is preferably more than 0.05wt.% of the silicone resin, preferably 0.1wt.% to 2wt.%, and more preferably 0.2wt.% to 1wt.%.
[0158] Table 3
[0159]
[0160] It can be seen from Examples 1, 9 and 10 that the use of other types of resins can also achieve effects substantially equivalent to those of Example 1.
[0161] Table 4
[0162]
[0163] It can be seen from the above table that, when other conditions are the same and only the amount of insulating additive added is different, as the amount of insulating additive added increases, the effective magnetic permeability of the metal soft magnetic material can be reduced and its DC bias performance can be improved; but the loss of the metal soft magnetic material first decreases and then increases with the increase in the amount of insulating additive added. Therefore, in order to obtain relatively high DC bias performance and lower loss, in the metal soft magnetic material of the present invention, the amount of insulating additive added is selected to be 0.5% or more, preferably 0.5% to 4%, and more preferably 0.7wt.% to 2.5wt.%.
[0164] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing an insulating auxiliary agent for a metallic soft magnetic material, characterized in that: It is made by ball-milling and compounding nano-scale fumed silica and silicone resin.
2. The preparation method according to claim 1, characterized in that: The amount of the nano-scale fumed silica is 0.05wt.% or more of the organic silicon resin, preferably 0.1wt.% to 2wt.%, more preferably 0.2wt.% to 1wt.%; And / or, the silicone resin is at least one of a polyalkyl silicone resin, a polyaryl silicone resin, and a polyalkylaryl silicone resin.
3. The preparation method according to claim 1 or 2, characterized in that: include: Dispersing nano-sized fumed silica in a solvent to form a slurry; The slurry is mixed with an organic silicone resin to obtain an insulating auxiliary agent; The nano-scale fumed silica is dispersed in the solvent by ball milling, and / or the slurry and the silicone resin are mixed by ball milling.
4. The preparation method according to claim 3, characterized in that: The ball milling time of the nano-scale fumed silica and the solvent is 2 to 6 hours; And / or, the solvent includes one or more of ethanol, propanol, and acetone; And / or, the ball milling time of the slurry and the silicone resin is 5 to 10 hours.
5. The preparation method according to claim 3 or 4, characterized in that: The nano-scale fumed silica is 1 wt.% to 10 wt.% of the weight of the solvent; And / or, the solid content of the silicone resin is 50% to 60%.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The rotation speed of the ball mill is 1500-2500 rpm.
7. An insulating auxiliary agent for metal soft magnetic materials, characterized in that: The preparation method is described in any one of claims 1 to 6.
8. A metal soft magnetic composite material, comprising metal soft magnetic powder, characterized in that: Also includes the insulating aid as claimed in claim 7.
9. The metal soft magnetic composite material according to claim 8, characterized in that: The added amount of the insulating auxiliary agent is 0.5% or more of the weight of the metal soft magnetic powder, preferably 0.5% to 4%, and more preferably 0.7% to 2.5%.
10. A metal soft magnetic core, characterized in that: The soft magnetic metal composite material is prepared by using the metal soft magnetic composite material according to claim 8 or 9.